A hybrid case-based reasoning approach to detecting the optimal solution in nurse scheduling problem. (1st October 2018) - Simić, Svetlana; Milutinović, Dragana; Sekulić, Slobodan; Simić, Dragan; Simić, Svetislav D; Đorđević, Jovanka
Abstract: Demand for healthcare is increasing due to a growing and ageing population. Choosing an adequate schedule for medical staff can be a difficult dilemma for managers. The goal of nurse scheduling is to minimize the cost of the staff while maximizing their preferences and the overall benefits for the unit. This paper is focused on a new hybrid strategy based on detecting the optimal solution in nurse scheduling problem. The new proposed hybrid approach is obtained by combining case-based reasoning and general linear empirical model with arbitrary coefficients. The model is tested with original real-world data set obtained from the Oncology Institute of Vojvodina in Serbia.